Agroforestry practices in Padawan, Sarawak - Syarifah Kamariah, bt. Wan Mohammad (2004)
Attaining agricultural sustainability remams at the forefront of Sarawak's challenges. Indigenous systems of agroforestry in Padawan have some potential in achieving this goal. This study illustrates the richness of existing heritage of agroforestry possessed by rural communities of Padawan, both predominantly subsistence and present-day urban agroforestry as practiced in conjunction with monocultural cash-cropping. Agroforestry practices located in five different locations within Padawan were observed and surveyed to describe the structure of the practices, to determine species of importance in the system and to ascertain the current soil quality of the system. Analysis of information from the field work and literatures has led to identification of a number of cultivated wild tree species, species that are of household utilization, localized economic, cultural and ecological importance in the Padawan agroforestry system. In consideration of the importance of to recognize the current soil quality in the agroforestry practices, indicators associated with soil quality include soil reaction (pH), soil organic carbon, bulk density, soil texture and structure are being studied. Sustainability and integration of agroforestry in Padawan is also discussed. The study concludes that richness and stability of Padawan agroforestry makes the area an important site for in-situ conservation of forest resources. More research on aspects not covered within the scope of this study is needed to enhance the state forest conservation and development projects.